RANCANG BANGUN BOX PENDINGIN IKAN BERBASIS PANEL SURYA DENGAN MENGGUNAKAN ELEMEN PENDINGIN PALTIER UNTUK KAPAL NELAYAN PESISIR - Fernando Saputra; Hidayatullah, Muhammad; Aulia, Masyitah; Jaya , Ahmad (Jurnal Altron, 2024)
From 2019 to 2020 there has been a decrease in fish catches. This is due to several causative factors, one of which is decay. Previously, some fishermen had to prepare many things to overcome decay even with preservation methods, most of which still use conventional methods in the form of using ice cubes. However, such methods are still lacking in terms of maintaining the quality of fish. Some have switched to using Cold Storage machines, but not all fishermen can afford to have them. So this is what made researchers conduct this study entitled "Design a Solar Panel-Based Fish Cooling Box Using Paltier Cooling Elements for Coastal Fishing Boats". The purpose of this research is to design and build a solar-powered cooling device as an energy source and help in a better preservation process at the desired temperature by relying on Paltier cooling elements. The research method used in this study is quantitative experiments for The results obtained from testing in this study were carried out 4 different test methods, but still reached the desired final temperature point of 5°C to 0°C and below.